DNA Isolation from Mammalian Samples. Issue 1 (1st April 2013) - Liu, Ximeng; Harada, Shuko
Abstract: DNA isolation is a fundamental initial step for molecular genetic studies. Two quite different methodologies are described in this unit: silica spin column and phenol/chloroform extraction. Currently, the most commonly used technique is the silica‐based spin column, although phenol/chloroform extraction is still widely used. This unit also presents basic procedures for extraction of DNA from both fresh tissues and formalin‐fixed, paraffin‐embedded (FFPE) tissue samples. Curr. Protoc. Mol. Biol . 102:2.14.1–2.14.13. © 2013 by John Wiley & Sons, Inc.